Digestible lysine for 63 to 103 day-old barrows of genetic lines selected for lean deposition - Fortes, Eduardo Ianino; Donzele, Juarez Lopes; Oliveira, Rita Flávia Miranda de; Saraiva, Alysson; Silva, Francisco Carlos de Oliveira; Souza, Matheus Faria de; Rocha, Gabriel Cipriano; Alebrante, Leandro (Revista Brasileira de Zootecnia, 2011)
Ninety-six barrows from 63 to 103 days of age were used to evaluate the effects of dietary digestible lysine levels on performance and carcass traits of two genetic lines selected for lean deposition. Pigs with initial body weight of 23.800 ± 1.075 kg were allotted in a completely randomized block design, within a 4 × 2 factorial arrangement (four digestible lysine levels: 0.80, 0.90, 1.00, 1.10%, and two genetic lines), with six replicates and two pigs per experimental unit. There was no interaction between genetic and digestible lysine levels. The digestible lysine levels also did not influence performance or carcass traits of pigs; however, average daily lysine intake increased with increasing digestible lysine level in the experimental diets. Pigs from genetic line B had better carcass traits when compared with those from genetic line A. The level of 0.80% digestible lysine corresponding to a daily intake of 16.60 g digestible lysine meets the nutritional requirement of pigs from both genetic lines evaluated, from 63 to 103 days of age.
Keywords: Amino acids; Carcass; Genotype; Growing; Performance